Approximate solutions for non-linear iterative fractional differential equations - Damag, Faten Hasan Mohammed; Kilicman, Adem; Ibrahim, Rabha Waell (AIP Publishing, 2016)
This paper establishes approximate solution for non-linear iterative fractional differential equations: dyv(s)/dsy = ℵ(s,v,v(v)), where γ ∈ (0, 1], s ∈ I := [0, 1]. Our method is based on some convergence tools for analytic solution in a connected region. We show that the suggested solution is unique and convergent by some well known geometric functions.